THE CHARACTER CONCEPT OF COURAGE (AS-SYAJA'AH) AND ITS IMPLEMENTATION IN ISLAMIC EDUCATION - Khairan Muhammad Arif (Program Studi Pengembangan Masyarakat Islam STID Mohammad Natsir, 2022)
The study of human character is a very important study in the global era, because almost all psychologists and modern education and human resource research recognize that positive character development really helps every organism or individual achieve success and improve the quality of human resources. Therefore, the purpose of this study is to prove that the types of characters in the Qur'an are superior characters and have been tested by history which have given birth to the great success of Muslims in the past. This study also aims to explore the noble and superior characters in the Qur'an in improving human resources. Among these characters is the character of courage (As-Syaja'ah). The method used in this study is a non-interactive qualitative method that focuses on literature studies (library research) integrated with historical studies (Historical Research) accompanied by the experiences of certain communities and in certain periods with analysis, re-interpretation and description according to context. and contemporary life. The results of this study are; know the types of positive and constructive character in Islamic education, namely courage and analysis of its implementation in the learning process in modern education. The benefit for educators, educational institutions and parents is to provide broad and superior insights and competencies for them in education.